Theoretical aspects of the intangible assets system in the process of enterprises strategic management: definition, characteristics, classifications - V. M. Sedelnikov (Вестник университета)
The article studies theoretical aspects of the intangible assets system in the process of enterprises strategic management. In particular, it highlights the points of view of Russian and foreign scientists regarding the definition of the intangible assets concept. The author’s definition of intangible assets as a set of a company’s resources and assets, which do not have a physical form, are used in the process of creating goods (services) for a long period of time (more than a year), are involved in the creation of values that provide a company a competitive advantage in the market and meet the requirements of identifiability (an object separation from other resources), the presence of future profits from their use, and direct or indirect control by a company. The basic criteria of intangible assets are identifiability, control over them, and the presence of future profits from their use. Despite the variety of available approaches in foreign literature to the intangible assets classification, in our opinion, the classification, which includes human, customer, and structural assets (capital), is fundamental. The article concludes that foreign authors shift their research focus from organizational (structural) intangible assets, such as corporate culture, organizational structure, and brand, to consumer and attitudinal (customer) ones, such as the level of customer satisfaction and loyalty and relationships value. The methodological approaches analysis to intangible assets assessment, the issues of their creation, modeling, and use by companies is a direction for further research.